Latin American trade relations. - CHRISTIAN, Shirley (1997)
Argues that formerly the US found Latin America worthy of attention only when the US decided to incorporate the region into efforts as solving US domestic problems, or needed firm support from the region in some international effort. Notes that today the US has to deal with Latin America as an equal, or see the region move forward alone with its own economic integration.